Emerging Exosomes and Exosomal MiRNAs in Spinal Cord Injury - Feng, Jia; Zhang, Yifan; Zhu, Zhihan; Gu, Chenyang; Waqas, Ahmed; Chen, Lukui (Frontiers in Cell and Developmental Biology, 2021)
Acute spinal cord injury (SCI) is a serious traumatic event to the spinal cord with considerable mortality and morbidity. The injury leads to short- and long-term variations in the spinal cord, and can have a serious effect on the patient’s sensory, motor, or autonomic functions. Due to the complicated pathological process of SCI, Currently, there is no successful clinical treatment strategy for SCI. Exosome, an extracellular vesicle with a double-layer membrane structure with a diameter of 30-150 nm, have recently been considered as critical mediators for communication between cells and tissues by transferring proteins, lipids, and nucleic acids. More studies verified that, the participation of exosomes in the pathophysiological process of several diseases such as cancer, neurodegenerative diseases and cardiovascular diseases, and could have a significant impact in their treatment. In this review article, we critically talked about the functions of exosomes as intracellular mediators and potential treatments in SCI, and we give an outlook to future researches.